Construction of Teaching Management Platform for Universities Based on Big Data - Guimei He (Advances in Multimedia)
The construction of the teaching management platform for colleges and universities needs to actively embrace information technology, change the problems existing in traditional offline teaching through technical innovation, make full use of massive educational resources, and improve teaching efficiency. However, no research has yet discussed how to handle the increasing scale of online teaching resources, leading to the hindrance of building teaching management platforms in universities, which requires the use of big data technologies and thinking to build new platforms. We propose a dynamic compression method to compress the data file backup in the database based on the dynamic adjustment of the system workload, and optimize the data file backup model of the database to reduce the total cost of ownership, which provides a basis for managing massive online education resources and building a teaching management platform for universities.